Assessment of patients referred to urgent start peritoneal dialysis: when does the nurse contraindicate? - Ferreira,Helen Caroline (2021)
Abstract Introduction: Urgent-start peritoneal dialysis (US-PD) has been used worldwide with very positive results. The prior assessment of candidates for this therapy by a nurse can favor the success of the therapy. Objectives: To identify the profile of patients who are candidates for US-PD, the causes of contraindication of the method by the nurse and their permanence in the method after 30 days, as well as the growth of the service after implementing the program. Methods: We retrospectively analyzed the forms used to assess candidates for US-PD applied by nurses between May 2017 and August 2019 in a clinic in Santa Catarina. We analyzed information on demographic profile, reasons for contraindication and permanence in the method after 30 days, as well as service growth after the program was implemented. Results: Of the 215 patients indicated for US-PD, 51% were male, 55% were under 60 years old, 51% had diabetes mellitus and 89% were hypertensive. Of these, 173 (80%) patients had the nurse’s approval for PD. The only cause contraindicated was the inability to self-care associated with the lack of family support. In the first 30 days after the assessment, 89% of the patients who started PD remained on it. During the study period, the PD service grew by 91%. Conclusion: During the study period, a fifth of patients referred to US-PD received contraindication by nursing due to self-care inability associated with the lack of family support. After 30 days, 89% of the patients remained on it.